Effect of Post Harvest Fruit Storage on Seed Quality in Ash Gourd (Benincasa hispida (Thunb.) Cogn.) - MURUGESAN. P; K. VANANGAMUDI (Seed Research, 2026)
Experiments were conducted during 2001-03 to find out the effect of post harvest storage of mature fruits of ash gourd (cvs. CO 2 and KAU Local) on seed quality. Stored fruits of CO 2 and KAU Local showed significant fruit weight loss of 52.9 and 49.9 per cent, respectively after one year. Similarly, fresh seed weight reduced to the tune of 23.3 and 11.5 per cent, and dry seed weight reduced to 24.6 and 25.4 per cent in CO 2, and KAU Local, respectively after one year of storage. The reduction of 100 seed weight was faster during 7-8 months onwards in KAU Local. The germination per cent significantly increased upto eight months of storage afterwards, a gradual decrease was observed in seed quality characteristics.